2020
DOI: 10.1002/mma.6508
|View full text |Cite
|
Sign up to set email alerts
|

The generalized quaternion matrix equation AXB+CXD=E

Abstract: In this paper, we discuss the generalized quaternion matrix equation AXB+CX⋆D=E, where X⋆ is one of X, X*, the η‐conjugate or the η‐conjugate transpose of X with η∈{i,j,k}. Two new real representations of a generalized quaternion matrix are proposed. By using this method, the criteria for the existence and uniqueness of solutions to the mentioned matrix equation as well as the existence of X=± X⋆ solutions to the generalized quaternion matrix equation AXB+CXD=E are derived in a unified way.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 26 publications
0
13
0
Order By: Relevance
“…The exosomes were refilled every two days when the medium was changed to avoid the degradation of exosomes. [ 56 ]…”
Section: Methodsmentioning
confidence: 99%
“…The exosomes were refilled every two days when the medium was changed to avoid the degradation of exosomes. [ 56 ]…”
Section: Methodsmentioning
confidence: 99%
“…[ 24–26 ] For instance, it has been proved that building a donor–acceptor (D–A) polymer structure is an efficient strategy to enhance the photocatalytic activity of organic polymer photocatalysts, since the electron push–pull system in a D–A polymer can enhance the separation of light‐induced electron/hole pairs. [ 27–29 ] The combination of a polycyclic aromatic donor and an electron‐withdrawing acceptor results in enhanced electron push–pull effect that further increases the separation capability of charge carriers, [ 30–33 ] leading to an enhanced photocatalytic activity. However, most reported D–A polymer photocatalysts are mainly based on polycondensation reactions from two functionalized monomers in stoichiometric ratio, which generates the copolymers with accurate alternative polymer structure.…”
Section: Introductionmentioning
confidence: 99%
“…Extracellular vesicles (EVs) are naturally occurring nanoparticles secreted by all cells, and serve important roles in many physiological processes, including immunomodulation 1. Increasing evidence has shown that therapeutic effects of cell therapy are elicited through the release of secreted EV cargo, such as RNA, proteins, and lipids 2–6. EVs have many advantages over cell therapy, including easier storage, eliminated risk of malignant transformation, prolonged circulation times, and increased stability 1.…”
Section: Introductionmentioning
confidence: 99%